DIGITAL MEDIA IN DEVELOPING CYBER COUNSELING SERVICES - Muhammad Farhan Azmi; Arifatuz Zahro; Afwan Syahril Manurung (Journal of Psychology, 2025)
This study aims to explore the role of digital media in the development of cyber counseling services, especially through the use of WhatsApp video calls, in increasing student self-disclosure during group counseling. The method used is a literature study, which is a systematic process of collecting, reviewing, analyzing, and synthesizing various written sources such as books, scientific journals, articles, and credible online publications. Through this approach, researchers build a strong theoretical foundation and understand the latest trends and findings related to the topic being studied. The results of the study show that digital media provides easy access, time flexibility, and allows the integration of advanced technology into counseling practices. However, challenges such as ethical issues, data security, and limitations of non-verbal interaction are still obstacles that need to be overcome. On the other hand, great opportunities are open through increasing digital literacy, innovation in therapy methods, and widespread mental health awareness campaigns. With the right approach, digital media-based cyber counseling services can be an effective and inclusive solution to meet the mental health needs of the community in the digital era. Keywords: Cyber ​​Counseling, Digital Media, Self-Disclosure, Data Security, Applied Innovation